Involvement of a novel Pseudomonas protegens strain associated with entomopathogenic nematode infective juveniles in insect pathogenesis. Issue 12 (19th September 2022) - Ruiu, Luca; Marche, Maria Giovanna; Mura, Maria Elena; Tarasco, Eustachio
Abstract: BACKGROUND: The bioinsecticidal action of entomopathogenic nematodes (EPNs) typically relies on their symbiosis with core bacteria. However, recent studies highlighted the possible involvement of other noncore species. We have recently isolated a novel Pseudomonas protegens strain as a major agent of septicaemia in larvae of the wax moth, Galleria mellonella, infected with a soil‐dwelling Steinernema feltiae strain. The actual role of this bacterium in entomopathogenesis was investigated. RESULTS: The association of P. protegens with nematodes appeared to be robust, as supported by its direct and repeated isolation from both nematodes and insect larvae infected for several consecutive generations. The bacterium appeared to be well‐adapted to the insect haemocoel, being able to proliferate rapidly after the injection of even a small amount of living cells [100 colony forming units (CFU)] to a larva, causing its fast death. The bacterium also was able to act by ingestion against G. mellonella larvae [median lethal concentration (LC50 ) = 4.0 × 10 7 CFU mL –1 ], albeit with a slower action, which supports the involvement of specific virulence factors (e.g. chitinases, Fit toxin) to overcome the intestinal barrier to the haemocoel. Varying levels of bacterial virulence were observed on diverse target Diptera and Lepidoptera. CONCLUSION: The soil‐dwelling bacterium P. protegens appears to have evolved its own potential as a stand‐alone entomopathogen, yet the establishment of an opportunistic association with entomoparasitic nematodes would represent a special competitive advantage. This finding contributes to a deeper understanding of the nematode–bacteria biocontrol agent complex and the deriving paradigm of their use as biological control agents. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : A novel strain of Pseudomonas protegens was found to be stably associated with the soil‐dwelling entomopathogenic nematode Steinernema feltiae . This noncore bacterium can act as a stand‐alone bioinsecticide or may take advantage of the vector nematode to reach the insect haemocoeal where it can proliferate.